Technology intervention to change the perception of acid mine drainage as energy - Setyo Moersidik, Yuli Sulistiyohadi, Iwa Garniwa,; Saria, Lana (Opción, 2020)
The purpose of this study is to build a model of social acceptance by technology intervention in acid mine drainage (AMD) treatment, by creating an electrification cell to process mine acid water into electrical energy. This research was done using a quantitative approach with exploring the perceptions of respondents from government, private, and community elements. As a result, the technology intervention has a significant change in the respondents' new perceptions of AMD. Technology interventions that process AMD into energy are able to change the perception of stakeholders about AMD. Besides, through technological interventions, AMD can meet future water needs too.